Internal Models, Subordinated Debt, and Regulatory Capital Requirements for Bank Credit Risk - Kupiec, Paul (IMF Working Papers; Working Paper ;, 2002)
Shortcomings make credit VaR estimates an unsuitable basis for setting bank regulatory capital requirements. If, alternatively, banks are required to issue subordinated debt that has a minimum market value and maximum acceptable probability of default, banks must set their equity capital in a manner that limits both the probability of bank default and the expected loss on insured deposits, largely removing any safety net-related funding cost subsidy and the moral hazard incentives it creates. Required equity capital can be estimated using a modified credit-VaR framework, and supervisors can use external credit ratings to indirectly verify the accuracy of bank internal model estimates.